Encryption of a Message by HillAli Cipher and Security of Routing Path by DSR in Wireless Sensor Network - Haneen Mohammed Hussein; Ali Qasim Hanoon; Afrah Thamer Abdullah (Journal of Communications Software and Systems)
A Wireless Sensor Network (WSN) is a collection of sensors that communicate or track a specific object. It is used in many fields of war, architecture, or espionage, but the wireless sensor network faces challenges in securing the path or the message, which is one of the most important problems to address through the routing process, this paper proposes using Dynamic Source Routing (DSR), which saves the path of message transmission and detects any compromised node to make a strong security process for the sent message or alert. It works by encrypting and decrypting the message. It mixes two ciphers, the Hill and Ali ciphers, which have been enhanced by incorporating a 4 * 4 matrix and supporting 2×2 and 3×3 matrices. The other cipher is the Ali cipher, as it depends on the use of the location of the letters in the message sent and the alphabet, generating a new hybrid cipher, the HillAli cipher.